2001
DOI: 10.2190/cxne-0ufr-7q04-cq3m
|View full text |Cite
|
Sign up to set email alerts
|

Methylphenidate in a Patient with Depression and Respiratory Insufficiency

Abstract: Methylphenidate may be useful for patients with severe medical conditions including ventilatory insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…A prospective trial of methylphenidate for negative symptoms such as anhedonia and psychomotor retardation in patients with Alzheimer's disease or vascular dementia64 reported significant improvement in symptoms scores, but did not provide response rates. Reports of successful uses of methylphenidate in the literature include treatment of lethargy and depressive symptoms in mechanically ventilated patients who are difficult to wean,75, 76 treatment of anorexia in apathetic, severely demented nursing home residents,77, and treatment of depressive symptoms in patients up to 106 years of age 78…”
Section: Resultsmentioning
confidence: 99%
“…A prospective trial of methylphenidate for negative symptoms such as anhedonia and psychomotor retardation in patients with Alzheimer's disease or vascular dementia64 reported significant improvement in symptoms scores, but did not provide response rates. Reports of successful uses of methylphenidate in the literature include treatment of lethargy and depressive symptoms in mechanically ventilated patients who are difficult to wean,75, 76 treatment of anorexia in apathetic, severely demented nursing home residents,77, and treatment of depressive symptoms in patients up to 106 years of age 78…”
Section: Resultsmentioning
confidence: 99%
“…The most frequent use was the combination of methylphenidate with citalopram in four trials for depression, showing significant improvement of the patients’ symptoms, as assessed by the Hamilton Depression Rating Scale [ 28 ], and good tolerability [ 29 - 32 ]. Other eleven trials were conducted for different conditions: post-stroke depression [ 33 , 34 ], Parkinson’s disease [ 35 , 36 ], falls [ 13 ] age-related cognitive decline [ 36 ], post-stroke rehabilitation [ 38 , 39 ], and medically-ill patients with depressive symptoms [ 40 - 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Psychostimulants appear to be reasonably safe even in those with respiratory insufficiency. 25 Although most experience improvement in target symptoms, some will experience worsening symptoms compatible with S/E so it is important to monitor symptom profiles in those on MP. Multiple studies have shown a low risk for MP abuse though caution should be used in those with a history of addiction.…”
Section: Discussionmentioning
confidence: 99%